2017
DOI: 10.1186/s12998-017-0165-8
|View full text |Cite
|
Sign up to set email alerts
|

The chiropractic profession: a scoping review of utilization rates, reasons for seeking care, patient profiles, and care provided

Abstract: BackgroundPrevious research has investigated utilization rates, who sees chiropractors, for what reasons, and the type of care that chiropractors provide. However, these studies have not been comprehensively synthesized. We aimed to give a global overview by summarizing the current literature on the utilization of chiropractic services, reasons for seeking care, patient profiles, and assessment and treatment provided.MethodsSystematic searches were conducted in MEDLINE, CINAHL, and Index to Chiropractic Litera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
213
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 190 publications
(222 citation statements)
references
References 303 publications
8
213
0
1
Order By: Relevance
“…Although chiropractors are legally recognized in 75% of those countries, and chiropractic treatment is fully or partially subsidized by national healthcare systems in around 50%, in some countries chiropractic does not fall under any law or may even be illegal [3]. Beliveau et al reviewed 52 studies dealing with utilization of chiropractic and found that, generally, utilization was highly variable and population dependent, with no clear change in utilization of chiropractors globally between 1980 and 2015 [4]. They found that the typical chiropractic patient is seeking care for a musculoskeletal The chiropractic profession: a scoping review of utilization rates, reasons for seeking care, patient profiles, and care provided.…”
Section: Papers Describing the Chiropractic Profession And Chiropractmentioning
confidence: 99%
See 1 more Smart Citation
“…Although chiropractors are legally recognized in 75% of those countries, and chiropractic treatment is fully or partially subsidized by national healthcare systems in around 50%, in some countries chiropractic does not fall under any law or may even be illegal [3]. Beliveau et al reviewed 52 studies dealing with utilization of chiropractic and found that, generally, utilization was highly variable and population dependent, with no clear change in utilization of chiropractors globally between 1980 and 2015 [4]. They found that the typical chiropractic patient is seeking care for a musculoskeletal The chiropractic profession: a scoping review of utilization rates, reasons for seeking care, patient profiles, and care provided.…”
Section: Papers Describing the Chiropractic Profession And Chiropractmentioning
confidence: 99%
“…To describe the chiropractic workforce worldwide in terms of the number of chiropractors, education, access, reimbursement schemes, scope of practice, and legal rights. problem, most commonly low back pain (50%) and neck pain (23%), is female, middle-aged and employed [4]. Although there is some variation in practice styles, most people seeking care from chiropractors will receive spinal manipulation with around one third also receiving patient education, exercises and soft-tissue therapy [4].…”
Section: Cross-sectional Surveymentioning
confidence: 99%
“…Chiropractors provide a significant portion of care for patients with low back pain [10], and care from chiropractors in the younger and older population appears to be safe and effective [11][12][13]. Unfortunately, existing trials have typically included only younger adults with low back pain, and exclude older adults for various complicating reasons, such as comorbidity and polypharmacy [14,15].…”
Section: Introductionmentioning
confidence: 99%
“…It is used to treat many musculoskeletal conditions, especially low back and neck pain [1]. Speci cally for chiropractors, SMT is the most common treatment provided during a patient encounter [2][3][4]. It is estimated that the 12month utilization rate for chiropractic services is 9.1% and a lifetime utilization of 22.2% worldwide [4].…”
Section: Introductionmentioning
confidence: 99%
“…Speci cally for chiropractors, SMT is the most common treatment provided during a patient encounter [2][3][4]. It is estimated that the 12month utilization rate for chiropractic services is 9.1% and a lifetime utilization of 22.2% worldwide [4]. Between 1980 and 2015, the use of chiropractic services has reportedly increased from 10.0% to 11.7% in Canada and from 7.2% to 10.7% in the United States [4].…”
Section: Introductionmentioning
confidence: 99%